2021
DOI: 10.1007/s10584-021-02971-y
|View full text |Cite
|
Sign up to set email alerts
|

Phenological tracking of a seasonal climate window in a recovering tropical island bird species

Abstract: Constraints on evolutionary adaptation and range shifts mean that phenotypic plasticity, which includes physiological, developmental or behavioural responses to environmental conditions, could be an important mode of adaptation to a changing climate for many species with small insular populations. While there is evidence to suggest adaptive plasticity to climate in some island populations, little is known about this capacity in species that have experienced a severe population bottleneck. In a changing climate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 59 publications
1
0
0
Order By: Relevance
“…Consistent with previous literature (Goodenough et al, 2010; Bowers et al, 2016; Taylor et al, 2021), we showed that mismatch, specifically laying eggs after the start of spring, decreased both nest success and productivity of American kestrels across their range. Geographic variation in strength of mismatch effects (i.e., stronger effects in the Northeast) may be related to variation in growing seasons and climate change impacts (Both et al, 2010; Garcia-Heras et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with previous literature (Goodenough et al, 2010; Bowers et al, 2016; Taylor et al, 2021), we showed that mismatch, specifically laying eggs after the start of spring, decreased both nest success and productivity of American kestrels across their range. Geographic variation in strength of mismatch effects (i.e., stronger effects in the Northeast) may be related to variation in growing seasons and climate change impacts (Both et al, 2010; Garcia-Heras et al, 2016).…”
Section: Discussionsupporting
confidence: 92%